Human papillomavirus, high-grade intraepithelial neoplasia and killer immunoglogulin-like receptors: a Western Australian cohort study - Brestovac, Brian; Wong, Michelle; Tjendera, Raymond; Costantino, Paul; Mamotte, Cyril; Witt, Campbell (BioMed Central, 2013)
Background: Human papillomavirus (HPV) is the causative agent in cervical cancer and HPV genotypes 16 and 18 cause the majority of these cancers. Natural killer (NK) cells destroy virally infected and tumour cells via killer immunoglobulin-like receptors (KIR) that recognize decreased MHC class I expression. These NK cells may contribute to clearance of HPV infected and/or dysplastic cells, however since KIR controls NK cell activity, KIR gene variation may determine outcome of infection.Methods: KIR gene frequencies were compared between 147 patients with a history of high-grade cervical intraepithelial neoplasia (CIN) and a control population of 187, to determine if any KIR genes are associated with high-grade CIN. In addition a comparison was also made between cases of high grade CIN derived from 30 patients infected with HPV 16/18 and 29 patients infected with non-16/18 HPV to determine if KIR variation contributes to the disproportional carcinogenesis derived from HPV 16/18 infection.Results: High-grade CIN was weakly associated with the absence of KIR2DL2 and KIR2DS2 (p = 0.046 and 0.049 respectively, OR 0.6; 95% CI 0.4 – 0.9) but this association was lost after correction for multi-gene statistical analysis.No difference in KIR gene frequencies was found between high-grade CIN caused by HPV 16/18 and non-16/18.Conclusion: No strong association between KIR genes, high-grade CIN and HPV genotype was found in the Western Australian population.